Bacterial predator-prey coevolution accelerates genome evolution and selects on virulence-associated prey defences - Ramith R. Nair (Nature Portfolio, 2019)
Predator-prey coevolution is expected to hasten evolutionary rates, but this is difficult to test in long-lived species. Here, the authors report consequences of experimental coevolution between bacterial predators and prey, including accelerated molecular evolution and parallel genomic and phenotypic adaptation.